Endovascular Debulking of Human Carotid Plaques by Using an Excimer Laser Combined With Balloon Angioplasty: An ex vivo Study - Yang, Kai; Tan, Jinyun; Deng, Ying; Shi, Weihao; Yu, Bo (Frontiers in Cardiovascular Medicine, 2021)
Purpose: We aimed to evaluate the safety and effectiveness of applying an excimer laser in debulking human carotid atherosclerotic plaques by investigating the distal debris, plaque luminal gain, and micromorphology of the plaque surface. Methods: Eighteen plaque samples obtained from carotid endarterectomy (CEA) were randomly allocated to the excimer laser ablation (45 mJ/mm2, 25 Hz) alone group (group 1), balloon angioplasty (8 atm) alone group (group 2), and excimer laser ablation combined with balloon angioplasty group (group 3). Hematoxylin–eosin staining and Movat's pentachrome staining were performed on the collected particles to quantify the size and composition of the debris. The superficial micromorphological structure of the plaque lumen surface after device treatments was observed using a scanning electron microscope. Micro-CT, tissue sections, and pathological stainings were applied to the treated plaques. The plaque lumen and artery lumen were three-dimensionally reconstructed using clinical computed tomography angiography and the micro-CT images. Lumen enlargement was set as the main measurement of effectiveness. Results: Group 3 produced the highest luminal gain (5.40 ± 4.51 mm2), while the other two groups had gains of 4.05 ± 3.20 and 3.77 ± 2.55 mm2. Both devices caused disruptions to the plaque lumen surface. Laser ablation exposed the fibers under the endothelium and balloon angioplasty cracked the surface. The mean amounts were 3,611 ± 1,475.4 for group 1, 2,828 ± 1,266.7 for group 2, and 4,400 ± 2,567.9 for group 3. More than 90% of the distal debris was smaller than 10 μm. Group 2 produced the most debris with Feret (maximum caliper diameter) ≥ 40 μm; group 1 had the least. There was little difference in the contents of collagen and reticular fiber in the debris in each group, but a big difference was observed in the contents of fibrin and mucin. Conclusion: Excimer laser ablation could significantly increase the luminal gain of carotid plaque with high stenosis. Excimer laser combined with balloon angioplasty achieved the highest lumen enlargement. Our result also suggests that the embolic protection strategy needs to be renewed for the application of a plaque debulking device in the future.